2023
DOI: 10.1038/s41598-023-31137-2
|View full text |Cite
|
Sign up to set email alerts
|

Population trends of striped hyena (Hyaena hyaena) in Israel for the past five decades

Abstract: The striped hyena (Hyaena hyaena) is considered “Near Threatened” globally and “Vulnerable” in the Middle East. In Israel, the species has experienced extreme population fluctuations owing to poisoning campaigns during the British Mandate (1918–1948) which were also further exacerbated by the Israeli authorities in the mid-twentieth century. We collated data from the archives of the Israel Nature and Parks Authority for the past 47 years to elucidate the temporal and geographic trends of this species. During t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Its individual range of activity is very wide and documented to reach 72 and 44 km 2 for males and females, respectively [ 47 ]. In Israel, an increase in hyena population density has been observed over the past few decades, with about two individuals per 100 km 2 compared to 0.06 individuals per 100 km 2 in the 1970s [ 48 ]. In contrast to the European badger, hyenas are less common reservoirs for human infections, with only a few reports of zoonotic pathogen infection in wild hyenas [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its individual range of activity is very wide and documented to reach 72 and 44 km 2 for males and females, respectively [ 47 ]. In Israel, an increase in hyena population density has been observed over the past few decades, with about two individuals per 100 km 2 compared to 0.06 individuals per 100 km 2 in the 1970s [ 48 ]. In contrast to the European badger, hyenas are less common reservoirs for human infections, with only a few reports of zoonotic pathogen infection in wild hyenas [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wild carnivore populations are expanding rapidly in many parts of Israel and encroaching into human habitation [ 48 , 58 ]. The potential role of wild carnivores as reservoirs of B. persica and their proximity to human settlements may be considered as a risk factor for human and companion animal infection, which control programs for TBRF should address.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, variations in the environment and population density are known to influence reproductive output [ 35 ]. Populations of striped hyenas in Israel have shown a marked increase along with exploitation of human resources [ 26 , 27 , 28 ], which could also influence reproductive output and breeding strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that no other studies have definitively reported—except for the one unpublished observation [ 25 ]—the relatively high occurrence of alloparenting by helpers in striped hyenas may be because it is, in general, a rare phenomenon across the species range. However, one must also take into account that the number of studies on breeding in striped hyenas is negligible to non-existent; most studies address the ecology—that is, food/prey [ 48 , 49 , 50 ], den locations [ 51 ], physiology [ 52 ], distribution and densities [ 53 , 54 ], threats and conservation [ 55 , 56 ], social interactions [ 45 , 57 ], population trends [ 26 ], human-hyena conflict [ 58 ], etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation